2009
DOI: 10.1177/1524838008331193
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Marital Conflict and Male Domination in the Family as Risk Factors of Intimate Partner Violence

Abstract: A systematic review was performed to analyse the characteristics and quality of the studies that consider the relationship between verbal marital conflict and/or male domination in the family and violent behaviour by men towards their partner. Only 11 articles were identified between 1986 and 2006. Most of them find a positive association between male domination in the family and/or verbal marital conflict and violence towards the woman in the couple. However, limitations such as misclassification bias, recall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 28 publications
0
9
1
Order By: Relevance
“…While previous studies examined perpetrators' high level of domination and low levels of anger management predictive of domestic violence (e.g. Vives-Cases et al, 2009), our study shows the lack of assertiveness and anger management on the part of the victim to be predictive of a high level of psychological aggression on the part of the perpetrator.…”
Section: Discussioncontrasting
confidence: 87%
“…While previous studies examined perpetrators' high level of domination and low levels of anger management predictive of domestic violence (e.g. Vives-Cases et al, 2009), our study shows the lack of assertiveness and anger management on the part of the victim to be predictive of a high level of psychological aggression on the part of the perpetrator.…”
Section: Discussioncontrasting
confidence: 87%
“…Hand searching is an additional method to minimize indexing errors (Petticrew & Roberts, 2006). Reference lists from previous partner aggression literature reviews were searched for additional studies that were possibly not captured in database searches (Archer, 2002; Foran & O’Leary, 2008; Schumacher et al, 2001; Stith et al, 2000; Stith et al, 2008; Stith, Smith, Penn, Ward, & Tritt, 2004; Vives-Cases, Gil-Gonzalez, & Carrasco-Portino, 2009; Williams, Ghandour, & Kub, 2008). When methodological aspects of a study were unclear (e.g., missing reporting of response rate), lead authors were contacted for additional information.…”
Section: Method: Systematic Reviewmentioning
confidence: 99%
“…At the personal level, substance abuse (Caetano et al 2005 ; Golinelli et al 2009 ; Hien and Ruglass 2009 ; Logan et al 2002 ), jealousy (Buss 2000 ; Wang et al 2009 ), anger management skills (Barbour et al 1998 ; Heru et al 2007 ), violence approval (Hien and Ruglass 2009 ; Margolin et al 1998 ; UNICEF 2009 ), dominance (Kim and Emery 2003 ; Straus 2006 , 2008 ), stressful conditions (Cascardi and Vivian 1995 ; Neff et al 1995 ), depressive symptoms (Danielson et al 1998 ; Lehrer et al 2006 ; Sugarman et al 1996 ), sexual abuse history (Daigneault et al 2009 ; Noll et al 2003 ; Whitfield et al 2003 ; Yoshihama et al 2009 ), and experience of witnessing parental IPV during childhood (Cloitre 1998 ; Hien and Ruglass 2009 ; Yoshihama et al 2009 ) were found to be significantly associated with the risk of IPV victimization. At the family level, relationship distress (Margolin et al 1998 ; Stuart and Holtzworth-Munroe 2005 ; Vives-Cases et al 2009 ), in-law conflict (Chan et al 2009 ; Clark et al 2010 ; Counts et al 1999 ), and financial burden or indebtedness (Balmer et al 2005 ; Chan et al 2008 ; Kempson et al 2004 ) are examples of factors related to IPV risk.…”
Section: Risk Factors For Ipvmentioning
confidence: 99%